The Next Generation Information Of Technology For Biodiversty Of Conservation - Sukoco A (Bandar Lampung University (UBL), 2017)
Monitoring and surveillance system in forest area is a system developed by implementing the achievement of technology and information to collect data and information in different ways. With the development of science, especially in the field of technology and information, especially in the development of the Internet of Things (IoT) increasingly provide opportunities to obtain information in real time, massive and accurate. ICT-related research for forest areas to be developed is an integrated system between forest ecosystems, buffer zones and urban areas through cloud computing systems involving integrated data centers for various data needs. IoT to be developed include: Visual Camera that can be used for surveillance of animals and vegetation, environmental sensors consisting of Weather Station, Temperature Sensor and Fire, GPS Sensor for Pal Limit. Access and data collection can use 450 Mhz point to point LTE BTS, or satelite at an economical price. Use for data.